PROFESIONALISME APARATUR BIROKRASI DI KECAMATAN BAOLAN KABUPATEN TOLITOLI - Lembah, Andi Irsyad (Katalogis, 2017)
The purpose of this study which determine the extent of the level of professionalism in the District Administrative Bureaucracy Baolan Tolitoli. The theory used to guide the analysis of the theory Professionalism is being addressed by siagian which consists of three aspects, namely responsiveness, innovation, and creativity. The type of data used are primary data and secondary data. Data collection techniques, carried out through observation, interviews, and documentation. Mechanical determination of informants in this study using purposive, where researchers deliberately chose informants in view of understanding the issues examined. Analysis of the data in the model used Miles and Huberman, namely data reduction, data presentation, and conclusion. Research results show that professionalism Apparatus In District Baolan Tolitoli not correspond with the expectations of society. This is evident from the three aspects of professionalism that is used in the object of responsiveness, innovation, and creativity.